Turkish Validity and Reliability Study of Challenge-Hindrance Demands Scale for the Nursing Profession - Handan Ertaş; Emel Fi̇li̇z; Şeyma Kahveci̇; Seda Nur Ünal (International Journal of Clinical Practice)
This study aims to adapt “the Challenge-Hindrance Demands Scale for Nursing Professional” developed by Mahaverachartkul and Sooraksa; regarding “how nurses who are under heavy workload and stress as well as intense and tiring working hours perceive many stressful situations in the working environment as challenges or hindrances” to Turkish language and bring it to the use of national literature. In terms of method, the research was designed within the scope of the quantitative research model. Data collected from 450 nurses were used in this study. The research data were analyzed in SPSS 26.0 and AMOS 24.0 statistical programs. The validity of the scales used in this study was evaluated with exploratory factor analysis (EFA) and confirmatory factor analysis (CFA). According to the EFA findings of the Challenge Demands Scale, when the KMO value (0.919) and the Bartlett sphericity test value (X2 (78) = 4121.203; p=0.001) were examined, it was seen that the data were suitable for analysis. When the CFA findings of the Challenge Demands Scale were examined, it was seen that the fit indices were at an acceptable level (X2 (60) = 223.912; p=0.001; CMIN/df = 3.732; CFI = 0.960; TLI = 0.948; RMSEA = 0.078; SRMR = 0.039). According to the EFA findings of the Hindrance Demands Scale, when the KMO value (0.947) and the Bartlett sphericity test value (X2 (78) = 5263.056; p=0.001) were examined, it was seen that the data were suitable for analysis. When the CFA findings of the Hindrance Demands Scale were examined, it was seen that the fit indices were at an acceptable level (X2 (61) = 208.794; p=0.001; CMIN/df = 3.423; CFI = 0.972; TLI = 0.964; RMSEA = 0.073; SRMR = 0.032). In conclusion, the Challenge-Hindrance Demands Scale for Nursing Professionals with 13 items and four dimensions developed to measure the stress, hindrance, and challenge levels of nurses in their professional life in Turkey may be used in future studies.